Analisis Faktor yang Mempengaruhi Rating Sukuk Syariah di Indonesia - Farhadi Arifiansyah; Safarinda Imani; Kholid Albar (Universitas Islam Lamongan, 2021)
Abstract: Sukuk is a form of investment and a means for companies to seek capital. Sukuk's issuance growth-increasing indicates that many investors are interested in buying Sukuk, so that many companies are also interested in issuing Sukuk. The more Sukuk issuances, the more important the rating of the Sukuk for investors and companies will issue Sukuk. The research aims to analyze the factors that affect the rating of Sukuk, such as corporate governance, financial ratios, market value, secure and types of Sukuk. The next goal is that the results of this study are expected to be a consideration for investors in determining investment in Sukuk and for companies to be considered in issuing Sukuk. This study uses secondary data obtained from the annual reports of corporate companies listed on the Indonesia Stock Exchange and rated by PT PEFINDO. The analysis technique in this study uses multinomial logistic regression with the SPSS 25. tool. The result of this study indicates that the CEO-Chairman Duality variable has a significant value of 0.037, the number of commissioners has a significant value of 0.001, commissioner independence is significant 0.035. Profitability has a significant value of 0.008, and leverage has a significant value of 0.044, liquidity has a significant value of 0.000. Market value using the stock price variable has a significant value of 0.006. The Secure variable has a significant value of 0.012. The type of Sukuk has a significant value of 0.000, so all variables in this study are considered to affect the Sukuk rating.